NURSES KNOWLEDGE, ATTITUDE AND PERCEPTION TOWARDS MENTAL ILL PATIENTS - MUSHTAQ , S; SADDIQUE , H; TASNEEM , SS; JABEEN , R (Biological and Clinical Sciences Research Journal, 2024)
Mental illness is a significant global health challenge, yet it remains stigmatized, particularly in low- and middle-income countries. Nurses, as frontline healthcare providers, play a crucial role in mental health care. Their knowledge, attitudes, and perceptions significantly influence the quality of care provided to individuals with mental illness. Objective: To assess the knowledge, attitudes, and perceptions of nurses toward mental illness in a tertiary care hospital in Lahore, Pakistan. Methods: A descriptive cross-sectional study was conducted among 152 nurses using a structured and validated questionnaire. Data were analyzed using SPSS version 26, with results presented as frequencies and percentages. Results: The study found that 48% of nurses had low knowledge regarding mental illness, while only 19.1% demonstrated high knowledge. Negative attitudes were prevalent, with 67.1% of nurses exhibiting stigmatizing views. Additionally, 67.8% of participants perceived individuals with mental illness as dangerous. Younger nurses and those with less experience displayed greater knowledge gaps and more negative attitudes. Conclusion: Despite moderate knowledge among some participants, negative attitudes and perceptions were widespread, highlighting the need for targeted educational programs and stigma-reduction initiatives. Comprehensive mental health training and policy reforms are essential to improve nursing practices and promote equitable mental health care.